2001
DOI: 10.2166/aqua.2001.0012
|View full text |Cite
|
Sign up to set email alerts
|

Does sunlight change the material and content of polyethylene terephthalate (PET) bottles?

Abstract: A simple water treatment process called SODIS (solar water disinfection) consists of filling polluted water in PET bottles that are exposed to sunlight for 5-6 hours. However, sunlight does not only destroy disease-causing microorganisms found in the water but also transforms the plastic material into photoproducts. Laboratory and field tests revealed that these photoproducts are generated at the outer surface of the bottles. No indication for migration of possible photoproducts or additives from PET bottles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(67 citation statements)
references
References 7 publications
4
58
1
3
Order By: Relevance
“…3, the sunlight radiation was lead to variation of COD amount of bottled water (increase from 342 to 460 mg L -1 during 30 days). Such variation can be attributed to the leaching of the compounds produced from the photodegradation of PET by sunlight (Wegelin et al 2001). Outdoor sunlight irradiation has been studied for its effects on organic compounds leaching.…”
Section: Chloridementioning
confidence: 99%
See 1 more Smart Citation
“…3, the sunlight radiation was lead to variation of COD amount of bottled water (increase from 342 to 460 mg L -1 during 30 days). Such variation can be attributed to the leaching of the compounds produced from the photodegradation of PET by sunlight (Wegelin et al 2001). Outdoor sunlight irradiation has been studied for its effects on organic compounds leaching.…”
Section: Chloridementioning
confidence: 99%
“…In sunlight exposure tests, Wegelin et al (Wegelin et al 2001) have shown that PET degradation products such as terephthalate monomers and dimers are primarily formed at the surface of the bottles. Peter Schmid et al (Peter Schmid et al 2008) sought to determine whether solar water disinfection (SODIS) would promote leaching of phthalates into water in PET bottles.…”
mentioning
confidence: 99%
“…[31][32][33] PET, the plastic that constitutes most SODIS bottles, is highly transmissive to 365 nm light, suggesting that psoralens could retain their photoreactive effects inside a PET bottle exposed to sunlight. 34 We selected three microorganisms to study based on their relevance to human disease. Escherichia coli are a thermotolerant coliform widely used in laboratory studies as a representative bacterial water contaminant.…”
Section: Introductionmentioning
confidence: 99%
“…SODIS reduces fecal contamination levels from 1 million bacteria per ml to zero in < 1.5 h, with consistency of the samples being studied; SODIS is completely effective against pathogens causing cholera, dysentery, typhoid, salmonellosis, gastroenteritis, cryptosporidi oasis, giardiasis and polio. This finding somewhat contradicts the recommendations provided by the Swiss Federal Institute for Environment and Technology (EAWAG, 1997) where Wegelin et al (2001) recommended five hours of exposure under bright sun or up to 50% cloudy sky, or two consecutive days fewer than 100% cloudy sky to be effective for disinfecting water.…”
Section: Discussionmentioning
confidence: 72%